1986
DOI: 10.1128/aem.51.1.201-202.1986
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of methanogens isolated from bovine rumen

Abstract: Six strains of methanogens were isolated from 10-8 and 10-9 ml of bovine rumen contents. All strains had the morphologic and physiologic characteristics of Methanobrevibacter spp. Four strains required coenzyme M; two did not. Growth of all strains either depended on or was stimulated by a mixture of isobutyric, isovaleric, 2-methylbutyric, and valeric acids. None of the strains reacted with antiserum against the type strain of Methanobrevibacter ruminantium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(20 citation statements)
references
References 6 publications
3
17
0
Order By: Relevance
“…In the present study, the observed promotion of the methanogenic population in diets supplemented with C 8 : 0 and C 10 : 0 may be due to the decline in numbers of protozoa, because these microorganisms also degrade Archaea to a certain extent (Newbold et al 1996). Moreover, Miller et al (1986) documented a stimulation of M. ruminantium growth by a mixture of isoacids, including isovalerate, which increased with C 8 : 0 treatment (Table 1).…”
Section: Fatty Acids and Microbial Populationssupporting
confidence: 53%
“…In the present study, the observed promotion of the methanogenic population in diets supplemented with C 8 : 0 and C 10 : 0 may be due to the decline in numbers of protozoa, because these microorganisms also degrade Archaea to a certain extent (Newbold et al 1996). Moreover, Miller et al (1986) documented a stimulation of M. ruminantium growth by a mixture of isoacids, including isovalerate, which increased with C 8 : 0 treatment (Table 1).…”
Section: Fatty Acids and Microbial Populationssupporting
confidence: 53%
“…users ml-l. The H2 users seen in positive tubes were all of the Methanobrevibacter morphotype (5). The dominant morphotype in the methanol MPN estimates was that of E. limosum, except that most of the tubes inoculated with the tion dilution contained clumps of the Methanosarcina morphotype.…”
Section: Resultsmentioning
confidence: 91%
“…stadtmanae and Mbb. smithii were species commonly reported in various studies from beef cattle and dairy cows by either culture‐based methods (Miller et al. 1986; Miller and Lin 2002) or molecular identification (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to their fastidious nature, only seven species of methanogens have been isolated from the rumen: Methanobacterium bryantii , Methanobacterium formicicum , Methanobrevibacter millerae , Methanobrevibacter olleyae , Methanobrevibacter ruminantium , Methanomicrobium mobile and Methanosarcina barkeri (Oppermann et al. 1957; Paynter and Hungate 1968; Miller et al. 1986; Jarvis et al.…”
Section: Introductionmentioning
confidence: 99%